2002
DOI: 10.1074/jbc.m108154200
|View full text |Cite
|
Sign up to set email alerts
|

A High Affinity HSF-1 Binding Site in the 5′-Untranslated Region of the Murine Tumor Necrosis Factor-α Gene Is a Transcriptional Repressor

Abstract: Tumor necrosis factor-␣ (TNF␣) is a pivotal early mediator of host defenses that is essential for survival in infections. We previously reported that exposing macrophages to febrile range temperatures (FRT) (38.5-40°C) markedly attenuates TNF␣ expression by causing abrupt and premature cessation of transcription. We showed that this inhibitory effect of FRT is mediated by an alternatively activated repressor form of heat shock factor 1 (HSF-1) and that a fragment of the TNF␣ gene comprising a minimal 85-nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
160
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 30 publications
12
160
0
Order By: Relevance
“…We and others have demonstrated that elements of the HS response are activated at febrile-range temperatures and regulate genes involved in inflammation and the innate immune response, including tumor necrosis factor α (Ostberg et al 2000;Singh et al 2002Singh et al , 2000, interleukin (IL)-1β (Cahill et al 1996;Fairchild et al 2000), IL-8, and granulocyte macrophage colony-stimulating factor (Rice et al 2005;Singh et al 2008), as well as HSPs. A computerassisted analysis of CXC chemokine promoters showed that almost every member of this family of neutrophil chemotaxins contains HSEs within their promoter sequences, suggesting these genes may be a newly recognized class of HSF-1-regulated genes (Nagarsekar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have demonstrated that elements of the HS response are activated at febrile-range temperatures and regulate genes involved in inflammation and the innate immune response, including tumor necrosis factor α (Ostberg et al 2000;Singh et al 2002Singh et al , 2000, interleukin (IL)-1β (Cahill et al 1996;Fairchild et al 2000), IL-8, and granulocyte macrophage colony-stimulating factor (Rice et al 2005;Singh et al 2008), as well as HSPs. A computerassisted analysis of CXC chemokine promoters showed that almost every member of this family of neutrophil chemotaxins contains HSEs within their promoter sequences, suggesting these genes may be a newly recognized class of HSF-1-regulated genes (Nagarsekar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To further analyze the relationship between temperature and activation of HSF-1, we analyzed the activation of HSF-1 to its intranuclear DNA-binding state by electrophoretic mobility shift assays (EMSA) using the well-characterized HSE sequence from the human HSP72 promoter as probe (Singh et al 2002. HSF-1-binding activities in nuclear extracts prepared from A549 cells maintained at 37°C or exposed to 42°C for 1 h, 39.5°C or 41°C for 1 or 6 h, or to 38.5°C for 1, 6, or 24 h were compared (Fig.…”
Section: Levels Of Intranuclear Hse-binding Activity Was Comparable Imentioning
confidence: 99%
“…Several pieces of evidence suggest a suppressive role of HSF1/hsp70 on TNFa-triggered inflammatory responses (Figure 9b, arrow e). Thus, activation of HSF1/hsp70 inhibits NF-kB activation [31][32][33] as well as transcription of the TNFa gene 34 Figure 9 Schematic mechanism of TNFa-mediated inhibition of HSF1/hsp70 and susceptibility to apoptosis. (a) The classical pathway of TNFa-mediated apoptosis involves TNF-R1 activation and signaling through caspase-8, which subsequently activates effector caspases, such as caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic Mobility Shift Assay-Nuclear extracts were prepared according to the method of Schreiber et al (38) as described earlier (37,39), and total protein concentration was measured. Double-stranded oligonucleotides containing the consensus HSF1 binding sequence from the human Hsp-70 promoter 5Ј-GATCTCGGCTGGAATATTCCCGACCTG-GCAGCCGA-3Ј and the complementary strands were synthesized, annealed, and radiolabeled with [␥-32 P]ATP using T4 polynucleotide kinase (Promega) according to the manufacturer's protocol (37,39).…”
Section: Methodsmentioning
confidence: 99%
“…Double-stranded oligonucleotides containing the consensus HSF1 binding sequence from the human Hsp-70 promoter 5Ј-GATCTCGGCTGGAATATTCCCGACCTG-GCAGCCGA-3Ј and the complementary strands were synthesized, annealed, and radiolabeled with [␥-32 P]ATP using T4 polynucleotide kinase (Promega) according to the manufacturer's protocol (37,39). Twenty-microliter EMSA reactions containing 5 g of nuclear extract, 0.035 pmol of radiolabeled oligonucleotide, 1 g of poly(IC), 10 mM Tris-HCl, pH 7.8, 10% glycerol, 60 mM NaCl, 1 mM EDTA, and 1 mM dithiothreitol were incubated at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%